ADULT EDUCATION FOR PEOPLE WITH EPILEPSY - MODIFICATION OF INTERNATIONAL EDUCATIONAL PROGRAM TO NATIONAL NEEDS - Šedienė, Polina; Pivoriene, Jolanta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the article is to discuss the process of piloting and modification of educational program for people with epilepsy, to present its implementation and country-specific evidence-based modifications which were influenced by sociocultural situation in the country and were made based on course’s participants experience. The article is grounded on the theoretical, legal documents analysis and data of participatory research with reflection of professional experience.The changes in the program in Lithuania were caused by specific sociocultural context in the country: there was lack of specialised psychosocial services for people with epilepsy, domination of biomedical model in treatment and services, recognition of disability in relation to working capabilities, high permanent unemployment, dependency of people with epilepsy on medical staff and family, lack of reflection skills, etc. The main modifications were: prolonged duration of the training and slowing the intensity of the training what gave possibility to train reflection skills; added new topics to the Program; the Program was complimented with participatory research. Participatory research revealed that made changes during the Program’s testing and modification process allowed participants to learn new skills, to tell illness narratives, to express hidden feelings, to take bigger responsibility for own illness, to formulate life goals and to plan next steps in life. The methodology of social pedagogy was used for the implementation of the Program, that it could meet the needs of the training participants and correspond to the national context.